Azospirillum brasilense as a bioinoculant to alleviate the effects of salinity on quinoa seed germination - Apaza Calcina, Jose David (2025)
Quinoa (Chenopodium quinoa Willd.) is valued for its resilience to abiotic stress; however, germination and seedling establishment remain highly sensitive to salinity. While its salt tolerance at later growth stages has been well studied, strategies to improve early development under high salinity are limited, and the role of halotolerant plant growth-promoting bacteria (PGPB) in quinoa has not been systematically investigated. This study assessed the ability of three Azospirillum brasilense strains (BR-11001, BR-11002, and BR-11005) to increase the germination and seedling performance of the cultivar 'BRS Piabiru' under saline stress. A 3 × 4 factorial design with three bacterial treatments and four NaCl concentrations (0, 150, 300, and 450 mM) was conducted in a completely randomized arrangement, with four replicates per treatment. Seeds were surface sterilized, inoculated, and incubated at 18 °C under constant light for 10 days. Elevated salinity (≥300 mM NaCl) drastically reduced germination and seedling vigor in the controls. Inoculation with BR-11002 significantly alleviated salinity-induced damage, sustaining over 84% germination at 450 mM and increasing seedling biomass at 300 mM. These findings highlight the potential of halotolerant A. brasilense, particularly BR-11002, as bioinoculants to promote quinoa establishment in salt-affected soils, supporting sustainable agriculture and food system resilience.